Improvement on step response in steam distillation process through of fuzzy based controller integrated PID anti-windup - Md Shariff, Haslizamri; Fazalul Rahiman, Mohd Hezri; Mazidah Tajjudin, Mazidah; Marzaki, Mohd Hezri; A. Jalil, Hafiz; Mohd Noh, Ku Siti Syahidah (UiTM Press, 2025)
The Proportional-Integral-Derivative (PID) controller is widely used in control systems due to its ease of development, tuning, efficiency, and reliable. However, it has a significant drawback known as the wind-up phenomenon, which occurs when the integrator action does not account for input saturation. This can lead to high overshoot and longer settling times, as the controller struggles to unwind the control input signal. Additionally, PID controllers often struggle to manage the nonlinear dynamics of Small-scale Steam Distillation Systems. This paper aims to develop a Fuzzy-based controller with an integrated anti wind-up strategy to improve system response. The Fuzzy controller is chosen due to its ability in regulate the nonlinear dynamics of the system. The anti wind-up strategy helps reduce overshoot and improve settling time, ensuring better temperature regulation. Simulation results demonstrate that the proposed Fuzzy-based controller integrated anti wind-up significantly outperforms the conventional PID controller. The Fuzzy integrated anti wind-up controller achieves an overshoot of less than 1%, while the PID controller exceeds 16%. Furthermore, the Fuzzy integrated anti wind-up controller has a settling time of under 4000 seconds, compared to over 7700 seconds for the PID controller.